Analysis of suitable converter for the implementation of drive system in solar photovoltaic panels - G. Themozhi; K. Srinivasan; T. Arun Srinivas; A. Prabha (Electrical engineering & Electromechanics, 2024)
Introduction. Photovoltaic (PV) systems gained immense attraction in the recent years since it produces electricity without causing environmental pollution through direct conversion of solar irradiance into electricity. Solar PV panels produce DC power. The magnitude of this DC power varies with temperature and irradiance of the sun rays. The DC supply from solar panels can be regulated using DC-DC converter and then can further be converted into the desired AC voltage by means of a voltage source inverter before being fed to an induction motor (IM). The speed and torque of an IM, fed from PV arrays, can vary due to the variation in the output power of the panels. Goal of this work is to improve the dynamic performance and reduce the torque ripple of Cuk converter-inverter fed IM drive system. The novelty of the current work proposes interleaved Cuk converter between solar PV DC source and the inverter. Purpose. To provide continuous current using an interleaved Cuk converter to the IM drive and in turn to reduce the torque ripple in IM. Methodology. Introduced an interleaved Cuk converter which is a blend of Cuk converters connected in parallel with each other between solar PV arrays and IM drive system. Originality. Simulation results are obtained for Cuk converter and interleaved Cuk converter fed IM drive by means of MATLAB. The hardware setup for the same IM systems is developed. Practical value. Simulation and hardware results are coincided with each other and it is subject from the simulation and hardware results that the interleaved Cuk converter-inverter fed IM system produced results superior than the Cuk converter inverter fed IM drive system.